1985
DOI: 10.1111/j.1600-0714.1985.tb00505.x
|View full text |Cite
|
Sign up to set email alerts
|

The permeability of hyperplastic oral epithelium

Abstract: An epithelial hyperplasia is one of the reactions of skin and oral mucosa to chemical and mechanical insult. It is usually assumed that this reaction produces a more effective epithelial harrier, but there is no information as to whether a less permeable (issue results. To examine this question, hyperplasia was induced in the cheek pouches of hamsters by either chemical treatment with 0.0025% TPA in acetone or by mechanical abrasion with a rotating mop; untreated hamsters served as controls. The animals were k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
7
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
(13 reference statements)
3
7
0
Order By: Relevance
“…The presence of a permeability barrier to the passage of lanthanum could be demonstrated in healthy rats; a finding in agreement with that of Squier and colleagues [21][22][23]. However, the maintenance of an epithelial barrier in the presence of an oral prosthesis has not been demonstrated previously.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The presence of a permeability barrier to the passage of lanthanum could be demonstrated in healthy rats; a finding in agreement with that of Squier and colleagues [21][22][23]. However, the maintenance of an epithelial barrier in the presence of an oral prosthesis has not been demonstrated previously.…”
Section: Discussionsupporting
confidence: 87%
“…The permeability barrier can be demonstrated ultrastructurally by the use of electron-dense materials such as lanthanum nitrate [23]. Hyperplasia, induced by turpentine or mild trauma has been shown to affect the permeability of oral epithelium [23]. No reports have been traced concerning the effects of infection on barrier function.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Permeation studies with horseradish peroxidase [5] and lanthanum nitrate [6] have shown that the flattened superficial layers constitute the major barrier, while the lower layers are relatively permeable. This is true in both keratinized and nonkeratinized epithelium, suggesting that keratinization does not offer as much resistance to buccal drug permeation as once thought.…”
Section: Epitheliummentioning
confidence: 99%